Device for measuring distance between flat / cylindrical and flat / flat surfaces - Gomes, Jotuanderson Pereira; Gomes, Laércio Gouvêa (Brazilian Journal of Production Engineering, 2026)
This study proposes a measuring device to determine the distance between flat/cylindrical and flat/flat surfaces with greater agility and precision, replacing the traditional tubular micrometer. The objective is to develop a device that reduces the operator’s skill dependency and increases measurement accuracy. Three measuring devices (tubular micrometer, tubular micrometer with accessory, and the developed device) were compared using combined uncertainty as a comparison parameter. Measurements were taken by volunteers with different levels of experience. The developed device showed a maximum measurement difference of 0.010 mm with an average time of 28.7 seconds, while the tubular micrometer showed a difference of 0.424 mm and an average time of 103 seconds. The developed device reduced data collection time and increased measurement accuracy compared to the tubular micrometer, meeting the proposed objectives.